?????????

Asked by hermionee | 29th Jan, 2009, 10:02: AM

Expert Answer:

let the elements of A matrix is a11,a12, a13.....that of B matrix is b11,b12,b13 .......and that of C matrix is c11,c12,c13......so on

as all matrices has same order so  Ist row of A - B is  [a11-b11 , a12 - b12 , a13 - b13 ]

and that of [A + C] - [B + C] = [ (a11+c11) - (b11 + c11)      (a12 + c12) - (b12 + c12)      (a13 + c13) - (b13 - c13)] ======> [a11-b11 , a12 - b12 , a13 - b13 ]

which is same as first row of A - B  so  A - B = A +C - B + C

Answered by  | 29th Jan, 2009, 06:20: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.